Yield and Economic Viability of Coriander under Frontline Demonstration in Bundi District of Rajasthan - Dhaka, B L; Poonia, M K; Meena, B S; Bairwa, R K (Journal of Horticultural Sciences, 2015)
A study was conducted in Bundi district of Rajasthan to analyze yield and economics of coriander under frontline demonstration. Results of the study revealed that yields in coriander were substantially higher over the Local Check (Control), fetching the participating farmers a higher price for their produce. A majority of the respondent farmers expressed high (44.32%) to very high (37.50%) level of satisfaction with extension services and performance of the technology under the demonstration.
Keywords: Coriander; Farmer; Frontline Demonstration; Yield